2019
DOI: 10.1128/iai.00339-19
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics Analyses Reveal Synergistic Carbohydrate Metabolism in Streptococcus mutans-Candida albicans Mixed-Species Biofilms

Abstract: Candida albicans, a major opportunistic fungal pathogen, is frequently found together with Streptococcus mutans in dental biofilms associated with severe childhood caries (tooth decay), a prevalent pediatric oral disease. However, the impact of this cross-kingdom relationship on C. albicans remains largely uncharacterized. Here, we employed a novel quantitative proteomics approach in conjunction with transcriptomic profiling to unravel molecular pathways of C. albicans when cocultured with S. mutans in mixed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 49 publications
1
77
0
1
Order By: Relevance
“…Mnn9, Van1, and Pmr1 contribute to mannan production, while Gca1 and Big1 regulate β-glucan synthesis (Mitchell et al, 2015), and the expression of genes was correlated with the synthesis of exopolysaccharide. Previous studies reported that S. mutans-derived GtfB binds to C. albicans surface mannan (Hwang et al, 2015), transcriptomic analysis of S. mutans-C. albicans mixed biofilms reveals that S. mutans enhances C. albicans carbohydrate metabolism and alters mannan and glucan production of C. albicans (Ellepola et al, 2019), and the C. albicans biofilm polysaccharide production results showed that exopolysaccharide levels and C. albicans secreted β-glucans were significantly increased in the S. mutans MV-treated group. These results are consistent with the observed upregulation in the expression of the abovementioned C. albicans genes.…”
Section: Discussionmentioning
confidence: 78%
“…Mnn9, Van1, and Pmr1 contribute to mannan production, while Gca1 and Big1 regulate β-glucan synthesis (Mitchell et al, 2015), and the expression of genes was correlated with the synthesis of exopolysaccharide. Previous studies reported that S. mutans-derived GtfB binds to C. albicans surface mannan (Hwang et al, 2015), transcriptomic analysis of S. mutans-C. albicans mixed biofilms reveals that S. mutans enhances C. albicans carbohydrate metabolism and alters mannan and glucan production of C. albicans (Ellepola et al, 2019), and the C. albicans biofilm polysaccharide production results showed that exopolysaccharide levels and C. albicans secreted β-glucans were significantly increased in the S. mutans MV-treated group. These results are consistent with the observed upregulation in the expression of the abovementioned C. albicans genes.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have shown that C. albicans is aciduric and acidogenic and is capable of biofilm formation, especially when grown in culture with S. mutans, resulting in increased amounts of extracellular polysaccharides (EPS) pertinent for caries development (23,29,40,81). Recent meta-omic analyses of S. mutans and C. albicans grown in mixed biofilms have provided molecular evidence to support the hypothesis that C. albicans enhances the cariogenic potential of S. mutans (28).…”
Section: Discussionmentioning
confidence: 99%
“…These glucans in turn increase the binding sites for S. mutans [13,17] resulting in a highly pathogenic mixed-species biofilm [15]. We demonstrated that S. mutans derived GtfB is able to augment the accumulation of C. albicans in mixed-species biofilms and enhance C. albicans growth by cross-feeding of glucose and fructose by sucrose breakdown [18,19]. Moreover, S. mutans was able to up-regulate the expression of C. albicans hypha associated genes such as HWP1, ALS1 and ALS3 which can be attributed to an increase in virulence of the organism in mixed-species biofilms.…”
Section: Introductionmentioning
confidence: 88%